A floristic study of a portion of the Pondoland Centre of Endeminism, Port St Johns, South Africa - Cloete, Elizabeth Carinus (Rhodes University, Faculty of Science, Botany Department, 2005)
Analysis of the flora of the Pondoland Centre of Endemism (PCE) recorded 2253 species in the combined checklist of four sites (Port St. Johns, Mkambati, Umtamvuna and Oribi Gorge). Of these 1 % species are endemic to Pondoland, representing 8.7% of the Species, 15% of the genera and 26% of the families of the combined flora. Forty-four percent ofthe combined flora was only recorded from one locality (between 17% and 26% of each flora) and only 12% of the flora was present in all four localities. Of the endemics only sixteen (8%) occurred in all four sites thus each site had its own complement of unique endemics and 21 % endemics were not recorded from any of the four sites. At species level the floras of Mkambati and Umtamvuna were the most similar, followed by that of Umtamvuna and Oribi Gorge. Port St Johns had the least in common with any of the othersites, but more in common with non-neighbours Umtamvuna and Oribi Gorge than with its nearest neighbour Mkambati. Mkambati and Umtamvuna had the largest proportion of PCE endemics and Port St Johns had the lowest. The four sites are quite similar at family level, sharing thirteen families in the top ten family list between them, but much less similar at generic level.
Keywords: Endemic plants -- South Africa -- Port St Johns; Phytogeography -- South Africa -- Port St Johns; Plants -- South Africa -- Port St Johns; Alien plants -- South Africa -- Port St Johns